Сетевой анализ при проектировании оптических транспортных информационных сетей - Хатнюк, И. С. (My University, 2009)
In this work we organized the analysis of the basic processes of optical transport informative Systems development; highways with temporal and spectral information compressions, which are actively utillized in main networks of the world and Ukraine, were analysed .
Keywords: сетевой анализ; проектирование оптических транспортных информационных сетей